2015
DOI: 10.1371/journal.pone.0141091
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation in Health Systems Research: A Systematic Review Assessing the State of Research, the Nature of Interventions Involved and the Features of Engagement with Communities

Abstract: BackgroundCommunity participation is a major principle of people centered health systems, with considerable research highlighting its intrinsic value and strategic importance. Existing reviews largely focus on the effectiveness of community participation with less attention to how community participation is supported in health systems intervention research.ObjectiveTo explore the extent, nature and quality of community participation in health systems intervention research in low- and middle-income countries.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
235
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(276 citation statements)
references
References 108 publications
(301 reference statements)
6
235
1
14
Order By: Relevance
“…These linkages were powerful ways to leverage community representation and address community needs, but only if communities were supported by networks and included in key mechanisms enabling and valuing bottom up planning. As noted previously, government mandates opening spaces for community participation are a key contextual factor, alongside the presence of social movements and the specific histories of collective experience and action specific to each community [2]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These linkages were powerful ways to leverage community representation and address community needs, but only if communities were supported by networks and included in key mechanisms enabling and valuing bottom up planning. As noted previously, government mandates opening spaces for community participation are a key contextual factor, alongside the presence of social movements and the specific histories of collective experience and action specific to each community [2]. …”
Section: Discussionmentioning
confidence: 99%
“…We undertook a secondary analysis of the documents identified through our previous systematic review on the nature of community participation in health systems interventions in low and middle income country contexts [2]. The database was constructed by searching for literature published from January 2000 to June 2012 in four electronic databases: Pubmed, Embase, Scopus/Web of Science, Global Health (Ovid) related to the concepts of “community”, “capability/participation”, “health systems research” and “LMIC”.…”
Section: Methodsmentioning
confidence: 99%
“…The findings that, in addition to individual-level factors, the community-level or group-level factors also have an impact on whether or not a woman is able to deliver in an institution, points to a need for greater investment and exploration into how to strengthen community capability, as well as community participation in health systems interventions [33]. The context in which a woman resides should be taken into account when designing programs and interventions to support institutional deliveries [34].…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies in low- and middle-income countries showed most to have near universal community support for the implementation of interventions. However, one-fifth of studies did not involve the community in participating in identifying or defining problems and community members for participation [33]. In coastal Kenya, community engagement activities using local residents addressed community myths towards biomedical research [34,35].…”
Section: Discussionmentioning
confidence: 99%